Die Auslöschung der Welt: Steven Millhausers Martin Dressler und die Architektur des amerikanischen Traums - Zeno Ackermann (Current Objectives of Postgraduate American Studies)
Critics such as Douglas Fowler have suggested that the work of Steven Millhauser deviates from current mainstream American fiction by daring to be "art for art's sake." At the same time, Millhauser's acclaimed 1996 novel Martin Dressler“ directly addresses and skillfully assesses the ideology of the "American dream." The essay shows how Millhauser's text - which paradoxically constitutes a fantastical novel of manners - uses the metaphor of architecture to integrate ideological concerns and aesthetic experimentation. Eventually, Martin Dressler “turns out to be a versatile critique of the cliché that capitalist enterprise realizes an excess of creative individualism.